2006
DOI: 10.1007/s00362-006-0009-4
|View full text |Cite
|
Sign up to set email alerts
|

Amputation versus imputation of missing values through ratio method in sample surveys

Abstract: In this article, we consider the estimation of population mean when some observations on the study characteristic are missing in the bivariate sample data. In all, ve estimators are presented and their e ciency properties are discussed. One estimator arises from the the amputation of incomplete observations while the remaining four estimators are formulated using inputed values obtained by the ratio method of estimation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…From Tables [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], it is noticed that the percent relative efficiencies of the suggested estimators involved in simulation studies for given the real data sets . It is found that our suggested imputation methods are more efficient than the mean method of imputation, ratio method of imputation, regression method of imputation, Singh and Horn [16] estimator, Singh and Deo [15] estimator, Toutenburg et al [18] estimators, Singh [17] estimator and Gira [5] estimator. Hence, the performances of the suggested methods and their corresponding estimators are highly justified in simulation studies which are shown in Tables [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] that may be recommended for further use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From Tables [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], it is noticed that the percent relative efficiencies of the suggested estimators involved in simulation studies for given the real data sets . It is found that our suggested imputation methods are more efficient than the mean method of imputation, ratio method of imputation, regression method of imputation, Singh and Horn [16] estimator, Singh and Deo [15] estimator, Toutenburg et al [18] estimators, Singh [17] estimator and Gira [5] estimator. Hence, the performances of the suggested methods and their corresponding estimators are highly justified in simulation studies which are shown in Tables [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] that may be recommended for further use.…”
Section: Discussionmentioning
confidence: 99%
“…The percent relative efficiencies of the proposed estimators τ i and η i (where i = 1, 2, ..., 22 ) with respect to the mean method of imputation, ratio method of imputation, regression method of imputation, Singh and Horn [16] estimator, Singh and Deo [15] estimator, Toutenburg et al [18] estimators, Singh [17] estimator and Gira [5] estimator respectively and computed as the followings:…”
Section: Simulation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Percentage Relative Efficiency (P.R.E.) of the proposed imputation methods with respect to the mean, ratio, compromised, [4] and [12] imputation methods, using equation 21, are reported in Tables 3-5…”
Section: Popmentioning
confidence: 99%
“…Various techniques for mean estimation under non-response have been considered by several researchers [3][4][5], among others. Some well-known imputation methods in literature are deductive imputation, mean imputation overall (MO), random imputation overall (RO), mean imputation within classes (MC), hot deck, cold deck and so on [6].…”
Section: Introductionmentioning
confidence: 99%